Combination of AAV-CCL19 and GPC3 CAR-T Cells in the Treatment of Hepatocellular Carcinoma - Min Meng; Yi-chen Wu (Journal of Immunology Research)
Background. Chimeric antigen receptor-modified T cell (CAR-T) therapy has great potential for treating malignant tumors, especially hematological malignancies. However, the therapeutic effect of solid tumors is limited. One of the most important factors is the homing of CAR-T cells to tumor tissues in vivo. Method. a recombinant adeno-associated virus 2 (AAV2) subtype carrying the CCL19 gene was used to pretreat the tumor before the Glypican-3 (GPC3) CAR-T treatment. The tumor tissue continuously expressed CCL19 and analyzed the tumor-suppressive effect of AAV-CCL19 on GPC3 CAR-T by in vitro and in vivo experiments. Result. Under the chemotaxis of CCL19, CAR-T cells had a significant increase in the degree of tumor tissue infiltration; also, the antitumor effect in vitro was significantly enhanced. AAV-CCL19 combined with GPC3 CAR-T significantly increased the survival time of mice. The aforementioned results showed that the combination of AAV-CCL19 and GPC3 CAR-T cells effectively increased the ability of CAR-T cells to go home into the tumor tissue, making the CAR-T cell treatment more effective. Conclusion. This study is expected to solve the dilemma in treating CAR-T cell solid tumors and achieve better clinical results.